Pengaruh Retail Mix Terhadap Customer Satisfaction Di Ace Hardward Tunjungan Plaza Surabaya - Richard Tanjaya (Jurnal Strategi Pemasaran, 2014)
This research aims to know the influence of the retail mix includes: Store Design and Display, Merchandise Assortment, Pricing, Communication Mix, Location, and Customer Service in order to achieve Ace Hardware Tunjungan Plaza Surabaya's customers satisfaction. In the sample examined are all consumers who have visited Ace Hardware Tunjungan Plaza Surabaya as much as 120 respondents. This research uses techniques of quantitative analysis with multiple linear regression analysis method.This research result shows that mix variable of retail Store Design and Display, Merchandise Assortment, Pricing, Communication Mix, Location, and Customer Service has a significant and positive impact on customer satisfaction. While the elements of the most dominant influence customer satisfaction is a merchandise Assortment.